Políticas públicas brasileiras de biocombustíveis: estudo comparativo entre os programas de incentivos à produção, com ênfase em etanol e biodiesel - Melo, Marcelo Caetano de Ribeiro e (2018)
The rising worldwide awareness of environmental questions and the Paris Accord's approval in 2015, during the COP 21, ensured the adherence of 195 countries and the ratification of 155 countries. Those countries committed to limit the average global temperature to 1.5 °C compared to the pre-industrial levels. The approval and such limitation, as well as the fact that cargo transportation is responsible for 23% of combustion-related gas emissions worldwide and 43% in Brazil alone, justified the present dissertation on its aim to talk about the Brazilian capacity on producing biomass that can be used on biofuel production, its several types, and mainly, which are the public policies implemented to promote the sector. The rising on renewable source-based fuel production is the most viable alternative in the short and medium-terms and this requires the compliance with the broad sustainability environmental, economic, social, technological and strategic requisites. Because of its soil and climate conditions, Brazil has a great biomass production potential and the added value to this raw material represents an important comparative advantage. Biofuel represents these possibilities given that the demand for energy tends to increase as the global economy keeps growing. It also has its energy derived from the fixation of biological carbon, and includes fuel derived from the conversion of biomass into liquid fuel and biogases. The Brazilian biofuel sector was stimulated due to the Proálcool. With the launching of a National Program for Production and Use of Biodiesel (PNPB, in the Portuguese acronym), in 2005, the biodiesel production has increased gradually in economic, social and environmental basis, aiming to contribute with the agroindustry strengthening, promote the reduction of regional disparities and foster both the industrial and the technological innovation policies. In the end of year 2017, Brazilian federal government sanctioned the bill that institutes the Biofuel National Policy, Renovabio. This public policy is one that aims to develop all kinds of biofuel in the country, respecting the sustainable development principles presupposed on the Paris Accord. This program differentiates itself from other policies by the fact that it does not aim to create more taxes. Quite the opposite, aims to encourage the competition with fossil fuel, guaranteeing quality and price to the consumer.